2020
DOI: 10.1177/2324709620941305
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Diarrhea in a Drinker: A Breakthrough Case of Pellagra in the US South

Abstract: The triad of diarrhea, dementia, and dermatitis constitutes the clinical diagnosis of pellagra. However, most reported cases of pellagra have occurred without all components of the triad. Pellagra was declared eradicated in the United States after an outbreak in the 1920s, and is now considered to be an exceedingly rare diagnosis in developed countries. In this article, we present a case of a 56-year-old man who presented with a significant history of alcohol use and chronic diarrhea. Pellagra was cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Pellagra is defined as a deficiency of niacin (vitamin B 3 ) and can be the result of malabsorption, excessive gastrointestinal (GI) loss, decreased intake, metabolic derangement or it can be drug induced 8. Nutritional deficiency causes primary pellagra while the secondary causes are unrelated to dietary deficiency (figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pellagra is defined as a deficiency of niacin (vitamin B 3 ) and can be the result of malabsorption, excessive gastrointestinal (GI) loss, decreased intake, metabolic derangement or it can be drug induced 8. Nutritional deficiency causes primary pellagra while the secondary causes are unrelated to dietary deficiency (figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary sources rich in niacin include liver, fish, eggs, milk, nuts and avocados 1. Niacin is a precursor for two coenzymes (nicotinamide adenine dinucleotide (NAD) and NAD-phosphate), crucial for cellular metabolism and DNA signalling 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic alcoholism leads to inhibition of tryptophan 2,3‐dioxygenase, a rate‐limiting enzyme of the hepatic kynurenine pathway of tryptophan degradation and niacin synthesis, resulting in pellagra 24 . Direct damage of intestinal villi may also lead to intestinal absorption of niacin and tryptophan, leading to pellagra in alcoholics 25 . Hiraga et al reported a rare case of laryngitis, glossitis and psychosis in a chronic alcoholic as a manifestation of pellagra 26 .…”
Section: Alcohol‐induced Pellagramentioning
confidence: 99%
“…People with alcohol abuse may face two problems: they don't eat well and their bodies struggle to obtain the nutrients they need. The primary purpose of examining this distinctive scenario is to underscore the pivotal importance of identifying and rectifying nutritional deficiencies among those who rely on alcohol [ 2 , 3 ]. This case also illuminates the intricate interplay between health conditions and lifestyle choices.…”
Section: Introductionmentioning
confidence: 99%